PENGARUH MODIFIKASI TERHADAP KARAKTERISTIK TEPUNG GADUNG (Dioscorea hipida Dennts.) TERMODIFIKASI : STUDI KEPUSTAKAAN - Maulidah, Hikmah; Wahyuni, Sri; Khaeruni, Andi (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2019)
ABSTRACT This review aimed to investigate the effect of the modification of the dioscoreas flour on the characteristics of the produced dioscoreas flour. In addition, this review also aimed to determine the composition of dioscoreas flour starch. Modification process of dioscoreas flour was done to improve the characteristics of flour produced. Modified dioscoreas flour also produced better flour properties than ordinary dioscoreas flour. The modification process can be done in several ways including through fermentation modification and using acid. The results of the review showed that the modification process (fermentation) was proven to improve the characteristics of dioscoreas flour better than using acid. Modified dioscoreas flour has the potential to substitute wheat flour in food processing. Keywords:Diocoreas flour, modification, characteristics of gadung flour. ABSTRAKReview ini bertujuan untuk melihat pengaruh perlakuan modifikasi tepung gadung terhadap karakteristik tepung gadung yang dihasilkan. Selain itu, review ini juga bertujuan untuk mengetahui komposisi pati tepung gadung. Proses modifikasi tepung gadung dilakukan untuk memperbaiki karakteristik tepung yang dihasilkan. Tepung gadung termodifikasi juga menghasilkan sifat tepung yang lebih baik dari tepung gadung biasa. Proses modifikasi dapat dilakukan melalui beberapa cara diantaranya adalah melalui modifikasi secara fermentasi dan menggunakan asam. Hasil review menunjukkan bahwa proses modifikasi dengan cara fermentasi terbukti dapat memperbaiki karakteristik tepung gadung lebih baik daripada menggunakan asam.Tepung gadung termodifikasi memiliki potensi untuk mensubtitusi tepung terigu pada pengolahan pangan. Kata kunci: Tepung gadung, modifikasi, karakteristik tepung gadung.